2022
DOI: 10.1080/20473869.2022.2070418
|View full text |Cite
|
Sign up to set email alerts
|

Inclusivity in education for autism spectrum disorders: Experiences of support from the perspective of parent/carers, school teaching staff and young people on the autism spectrum

Abstract: Inclusive practices mean many children with autism spectrum disorders (ASD) attend mainstream education settings. To manage the stressors involved and access its benefits, support can be critical. Indeed, insufficient support can detrimentally impact wellbeing, longer-term development, and the inclusivity agenda. Expanding a limited evidence-base on educational support after diagnosis, focus groups and interviews were conducted for eight parent/carers of children with ASD, twelve special education needs (SEN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…This is consistent with other, recent, studies in which researchers have found that prior to their transition to secondary school, most children with ASD worry about the size of their prospective schools and the sensory difficulties (particularly the noise) they will encounter (Makin et al, 2017). Moreover, in another study, young people with ASD expressed a strong need for schools to provide a quiet space in which the noise could be avoided (Hasson et al, 2022). Providing access to such spaces might help decrease the stress and anxiety levels that these students experience (Lebenhagen, 2022), and support their mental health and well-being, which is, according to parents in a recent study, negatively affected by mainstream education experiences (McKinlay et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other, recent, studies in which researchers have found that prior to their transition to secondary school, most children with ASD worry about the size of their prospective schools and the sensory difficulties (particularly the noise) they will encounter (Makin et al, 2017). Moreover, in another study, young people with ASD expressed a strong need for schools to provide a quiet space in which the noise could be avoided (Hasson et al, 2022). Providing access to such spaces might help decrease the stress and anxiety levels that these students experience (Lebenhagen, 2022), and support their mental health and well-being, which is, according to parents in a recent study, negatively affected by mainstream education experiences (McKinlay et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, this research found that teachers encounter funding difficulties when it comes to the need for teaching resources and assistive technology devices for their students with ASD. This finding is supported by that of Hasson et al (2022) , who stated that students with ASD must receive the necessary funding to ensure they are well-educated ( Lindsay et al, 2013 ; Hasson et al, 2022 ). In the case of private schools, such as that involved in this study, it is necessary that such programs seek funding from appropriate entities, such as state and federal government agencies, to ensure the availability of necessary resources for students with ASD.…”
Section: Discussionmentioning
confidence: 75%
“…Such additional training has also found that the confidence and knowledge was higher in teachers working with students with ASD after they had completed effective trainings on fundamental ABA techniques ( Leblanc et al, 2009 ). Given that teacher preparation programs have been found to be lacking in how they prepare (or fail to) teachers to work with students with ASD, teachers must have access to professional development that trains them in EBPs to support these students ( Hsiao and Sorensen Petersen, 2019 ; Hasson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these increases, recent OFSTED (2018OFSTED ( , 2022 reports have found that provision for these students is disjointed and inconsistent. Mainstream inclusion does create dilemmas for parents of students with SEND who can be overwhelmed by the burden of choosing a setting for their child, lacking support in decision-making or experiencing an illusion of choice which is ultimately removed through lack of funding or geographical constraints (Flewitt & Nind, 2007;Hasson et al, 2022).…”
Section: Current Landscape and Prior Researchmentioning
confidence: 99%